Defective interfering particles mediated early protection in animals against rinderpest* - DHAR, P; BANDYOPADHYAY, S K (The Indian Journal of Animal Sciences, 2014)
Defective interfering (DI) particles were generated out of 4 serial undiluted passages of tissue culture rinderpest virus in vero Cells, leading to a persistent infection. These persistently infected cells supposedly contained DI particles that interfered with the replication of standard rinderpest virus, as detected in an in vitro interference assay. A preparation of such DI particles (the stock containing 5.85 x 106 particles/ml) was inoculated into rabbits and cattle and challenged animal were protected from the disearse, whereas simlar early protection was not evident with the live attenuated rinderpest vaccine. Use of such an approach in speedy control of diseases in field condition seems plausible.